‘With a Little Help from My Friends’: The Dutch Solidarity Movement and the Chilean Struggle for Democracy - Perry, Mariana (European Review of Latin American and Caribbean Studies, 2016)
This article explores the political interaction that took place during the 1970s and 1980s between Chilean refugees and the local solidarity movement in the Netherlands. The analysis of the Dutch political context during the 1970s facilitates an understanding of the positive reception of Dutch society to Chilean refugees and the long-lasting impact that the Chilean case had on Dutch politics. The article also asserts that though Dutch solidarity was essential for maintaining international attention in denouncing the Pinochet regime, the international dimension for redemocratization began when the Chilean community in exile organized itself according to democratic principles. In this sense, the article places the foundation of the Institute for a New Chile as the main contribution of the Netherlands to the democratic transition in Chile, since in the space provided by the Institute, Chilean refugees could debate and spread the ideas of ‘Renovation’, in an atmosphere of political tolerance. This ultimately contributed to the unification of a democratic opposition in exile and the decision to defeat the Pinochet regime through democratic means. Resumen: ‘Con un poco de ayuda de mis amigos’: El movimiento holandés de solidaridad y la lucha chilena por la democracia Este artículo explora la interacción política que tuvo lugar durante los años 1970 y 1980 entre los refugiados chilenos y el movimiento de solidaridad en los Países Bajos. El análisis del contexto político holandés durante la década de 1970 permite entender la buena acogida que la sociedad holandesa tuvo con los refugiados chilenos y el impacto duradero que el caso chileno causó en la política holandesa. Además el artículo afirma que, si bien la solidaridad holandesa fue esencial para mantener el compromiso internacional en denunciar al régimen de Pinochet, la dimensión internacional de la redemocratización comienza cuando la comunidad chilena en el exilio se organiza en torno a principios democráticos. En este sentido, el artículo sitúa la fundación del Instituto para una Nueva Chile como la mayor contribución de los Países Bajos a la transición democrática en Chile, ya que en el espacio provisto por el Instituto, los refugiados chilenos debatieron y difundieron las ideas de la Renovación, en un ambiente de tolerancia política. Esto finalmente contribuyó a la unificación de una oposición democrática en el exilio y en la decisión de derrotar al régimen de Pinochet a través de medios democráticos.